Analysis of Affixation on “Bertaut” Song Lyrics by Nadin Amizah: a Morphological Study - Ade Kusmana (Departement of Mathematics Education, 2021)
This research was conducted using qualitative methods. The data used is taken from the lyrics of Nadin Amizah's song on the song entitled